Supply Chain Resilience: Strategies for Mitigating Disruptions and Building Adaptive Networks - Maemunah, Siti (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to investigate strategies and best practices for improving supply chain resilience. Through a systematic literature review approach, four main strategic areas have been identified, namely supplier diversification, supply chain visibility, production disruption management, and digital technology integration. The findings show that supplier diversification is a crucial strategy in mitigating negative impacts during periods of disruption, while increasing supply chain visibility and effective management of production disruptions also play an important role. The integration of digital technology stands out as a key factor in managing supply chains effectively, especially in the face of non-tariff barriers in the industry. The practical implications of these findings provide valuable guidance for supply chain practitioners and managers in developing more adaptive and effective strategies in facing the challenges of an increasingly complex business environment.